Role of Salmonella Typhi Vi Antigen and Secretory Systems on Immune Response - Schadich, Ermin; Dzubak, Petr; Hajduch, Marian (Current Pharmaceutical Design, 2016)
Virulence capsular polysaccharide (Vi antigen) and Salmonella`s Pathogenicity Island type 1 and 2 TTSS (SPI-1 and SPI-2 TTSS) are important membrane virulence factors of human restricted pathogen S. Typhi. The Vi antigen modulates different proinflammatory signaling pathways in infected macrophages, microfold epithelial and dendritic cells. SPI-2 TTSS and its effectors are required for promoting bacterial intracellular survival, replication and apoptosis while SPI-1 and its effectors are associated with invasion of microfold epithelial cells. The purified Vi-antigen has been used as a vaccine against disease. It is a T cell independent antigen that induces moderate efficacy ( 55%) in adults and no efficacy in children bellow two years of age. Carrier protein conjugation of the Vi antigen has been successfully used to confer T cell dependency and to develop Vi conjugate vaccines with high efficacy, around 89% in three years, in all age groups. So far, the attenuated live vaccine with constitutive expression of Vi antigen and the SPI-2 TTSS mutant vaccine, progressed to phase 3 clinical tests. Particularly, the live attenuated vaccine with constitutive expression of Vi antigen might be also used to optimize the efficacies of other vaccines. The current preclinical studies consider also development of novel T cell independent vaccines from recombinant proteins and generalized modules for membrane antigens. An approach for future antivirulence therapy against disease might also consider the bioactive compounds with ability to inhibit TTSS secretions. It is concluded that combined approaches my successfully reduce S. Typhi infection in this new globalized era.
Keywords: Salmonella typhi